Implications of efficiency and productivity change over the season for setting MEY‐based trigger targets1. (26th December 2017) - Pascoe, Sean; Hutton, Trevor; Coglan, Louisa; Nguyen, Van Quang
Abstract : The banana prawn component of Australia's Northern Prawn Fishery (NPF) is currently managed through the use of annually updated trigger catch rates as a means of achieving maximum economic yield (MEY) in the fishery, taking into account the estimated price and cost components for that season. The estimation of these target catch rates is based on the assumption of relative homogeneity of the fleet in terms of efficiency, productivity and cost structure. In this study, these assumptions are examined through the estimation of a stochastic production frontier. While technical efficiency varies between vessels, average efficiency is relatively constant over the fishing season. However, average productivity of the fleet increases, with smaller vessels (in terms of engine power) exiting the fishery earlier. This would likely increase the average cost of fishing towards the end of the season, with implications for setting the target catch rate. Based on a standard assumption as to the relationship between costs and vessel size, we find that the MEY target catch rates are most likely currently underestimated. However, the implementation of a precautionary minimum catch rate (which is above the MEY target catch rates for recent years) has maintained the fishery at a profitable level.